Aquatic plants and benthic biodiversity: A comprehensive study of community interactions in Aneuk Laot Lake, Sabang - Nurfadillah Nurfadillah; S Darmarini Ananingtyas; Kamal Ahmad; Annisa Annisa; Ediansa Putra Nanta; Maulida Siti (BIO Web of Conferences)
Aquatic plants, as primary producers, play a crucial role in aquatic ecosystems, and macrozoobenthos also contribute significantly to the nutrient cycles at the water's bottom. This research aims to identify and analyze aquatic plants and macrozoobenthos in Aneuk Laot Lake, Sabang. This research uses a descriptive method by analyzing the diversity index, uniformity index, dominance index and species abundance. The research results show that there are 3 families, 5 species and 94 individuals of aquatic plants. The most dominant species is Eichhornia crassipes from the Pontederiaceae family. The abundance value of aquatic plants in Lake Aneuk Laot ranges from 13-26 individuals/m2. The aquatic plant diversity index ranges from 1.48-1.58, which indicates the medium category. The aquatic plant uniformity index ranges from 0.92-0.98 which indicates the stable category and the dominance value ranges from 0.21-0.24 which indicates the low category. The macrozoobenthos composition consists of 3 classes, 7 species and 82 macrozoobenthos individuals. The most dominant species is Anodonta woodiana from the Unionida family. The highest abundance in macrozoobenthos ranges from 5-23 individuals/m2. The macrozoobenthos diversity index ranges from 0.95-1.46 which indicates the medium category. The uniformity value ranges from 0.87 to 0.91, which is in the high category, and the dominance index ranges from 0.26 to 0.40, indicating good stability in the macrozoobenthos community. The value of the commodity structure of aquatic plants and macrozoobenthos shows that water conditions are stable and the diversity index of aquatic plants and macrozoobenthos is classified as moderate, uniformity is still evenly distributed and there are no dominant species.